Music Movement Therapy for Improving Muscle Strength in a Non-Hemorrhagic Stroke Patient: A Case Study at Bayu Asih Hospital - Ratna Wulan Hardian Noviani; Agus Mardiansyah; Emmy Salmiyah (Jurnal Kesehatan Budi Luhur: Jurnal Ilmu-Ilmu Kesehatan Masyarakat, Keperawatan, dan Kebidanan, 2025)
Stroke is a cerebrovascular disease that causes neurological and motor impairments, often leading to reduced muscle strength. Music Movement Therapy (MMT) is a non-pharmacological intervention combining music and range-of-motion (ROM) exercises, which may improve muscle strength and support rehabilitation in stroke patients. This case study was conducted from 13–19 March 2024 on a non-hemorrhagic stroke patient (Mrs. M) at the Teratai Room of Bayu Asih Hospital, Purwakarta. The patient received MMT sessions for 15 minutes daily over three consecutive days. Muscle strength was measured before and after the intervention using Manual Muscle Testing (MMT scale). Muscle strength improved from grade 2 (full joint motion without resistance) on day 1 to grade 4 (able to resist light to moderate resistance) on day 3 after the intervention. MMT effectively increased upper-extremity muscle strength in this non-hemorrhagic stroke patient. Health professionals may consider MMT as a complementary non-pharmacological intervention to enhance motor function in stroke rehabilitation.